Importance of glucose-6-phosphate dehydrogenase in the adaptive response to hydrogen peroxide in Saccharomyces cerevisiae. - Izawa, S (1998)
Glucose-6-phosphate dehydrogenase (G6PDH)-deficient cells of Saccharomyces cerevisiae showed increased susceptibility and were unable to induce adaptation to oxidative stress. Historically, mainly in human erythrocytes, it has been suggested and accepted that decreased cellular GSH, due to loss of the NADPH-dependent activity of glutathione reductase (GR), is responsible for the increased sensitivity to oxidative stress in G6PDH-deficient cells. In the present study we investigated whether the increased susceptibility and the inability to induce adaptation to H2O2 stress of G6PDH-deficient yeast is caused by incompleteness of glutathione recycling. We constructed G6PDH- and GR-deficient mutants and analysed their adaptive response to H2O2 stress. Although G6PDH-deficient cells contained comparable amounts of GSH and GR activity to wild-type cells, GSSG was not reduced efficiently, and intracellular GSSG levels and the ratio of GSSG to total glutathione (GSSG/tGSH) were higher in G6PDH-deficient cells than in wild-type. On the other hand, GR-deficient cells showed a susceptibility identical with that of wild-type cells and induced adaptation to H2O2 stress, even though the GSSG/tGSH ratio in GR-deficient cells was higher than in G6PDH-deficient cells. These results indicate that incompleteness of glutathione recycling alone is not sufficient to account for the increased sensitivity and inability to induce adaptation to H2O2 stress of G6PDH-deficient yeast cells. In S. cerevisiae, G6PDH appears to play other important roles in the adaptive response to H2O2 stress besides supplying NADPH to the GR reaction.